The effects of seed grading, polishing and air-separation on some important seed characters of sugar beet momogerm cultivar Gadouk seed - محمد علی چگینی; مهدی اتحاد (علوم و فناوری بذر ایران)
The effects of seed grading in 6 levels (3.25 to 5.5 mm), seed polishing in 5 levels (10 to 35 percent of original weight) and sorting out empty seed in 5 levels (10 to 50 percent of original weight) on germination by using gadouk monogerm seed in a completely randomized desigh with 4 replication were investigated. Results showed that 1000 seed weight vary from 7.18 up to 27 g. By increasing round sieve dimensions 1000 seed weight incresed. However, germination increased by increasing 1000 seed weight up to 14 g and over weight had no effect on germination. Seed polishing decreased one-thousands seed weight. Germination was increased by discharging small seed size. Germination was increased (especially small seed size) when less than 20 percent of initial seed lot weight was omitted by polishing treatment. However, when more than 20 percent of initial seed lot weight was omitted by polishing treatment germination was decreased, abnormal seedling and decapped fruit were increased. When empty seed was separated by air, germination of small and large seed increased up to 15 and 2 percent, respectively. Removing more than 20 percent of initial seed lot weight by air-separation had no effects on germination